Analisis Kepuasan Pelanggan dengan Menggunakan SERVQUAL: Studi Kasus Layanan IndiHome PT. Telekomunikasi Indonesia, Tbk, Regional 1 Sumatera - Ulkhaq, M. Mujiya; Br. Barus, Monalisa Putri (Jurnal Sistem dan Manajemen Industri, 2017)
As competition increases, delivering better service becomes more important; it is not with the expception of PT. Telekomunikasi Indonesia, Tbk (PT TELKOM), which is the only state-owned enterprise as well as the largest telecommunication and network service provider in Indonesia. This is because service quality is considered as an important aspect for the success of the service provider. This study aims to assess the service quality of PT. TELKOM for IndiHome products. A preliminary study showed that there are many customers complaining about IndiHome's service quality. In addition, the tight competition and the emergence of several similar service providers as well as attractive promotion will inevitably attract customers not to be loyal if PT. TELKOM does not immediately improve the quality of the service. This research was conducted not only to assess the service quality of IndiHome (using SERVQUAL), but also to give some recommendations to PT. TELKOM especially Regional 1 Sumatra in order to attain customer satisfaction. There were 153 respondents who participated in this study. The results show that on average, customers are not satisfied (the gap value is 1.539). This negative value means that the customers have high expectations of the services that should be delivered by PT. TELKOM, but in reality the performance of the service is not as high as their expectations. Therefore, some recommendations are given to improve the performance of IndiHome service quality so that the customers are satisfied.